Comparison of En Bloc Resection and Intralesional Excision for Re‐resection of Giant Cell Tumors of the Spine - Hua Zhou; Yanchao Tang; Panpan Hu; Shuheng Zhai; Xiaoguang Liu; Zhongjun Liu; Feng Wei (Orthopaedic Surgery, 2024)
Objective Re‐resection of spinal giant cell tumors is an exceedingly difficult procedure. Moreover, the prognosis of patients with en bloc resection or intralesional excision for re‐resection has rarely been reported. This study aimed to compare the prognostic value of en bloc resection with that of intralesional excision in patients undergoing re‐resection for giant cell tumors of the spine. Methods This retrospective analysis evaluated patients who underwent revision surgeries for relapse of giant cell tumors of the spine at our center between January 2005 and January 2021. Local progression‐free survival represents the duration between en bloc resection or intralesional excision and tumor recurrence. Neurological recovery, survival rates, local control, and complications were evaluated. The Kaplan–Meier estimator was used for survival analysis. Results A total of 22 patients (nine men and 13 women) with a mean age of 34.1 (range 19–63) years were included. Significant statistical differences were found in the local tumor recurrence rate between patients treated with en bloc resection and those treated with intralesional excision (p < 0.05). The 5‐ and 10‐year local progression‐free survival rates were both 90% in the en bloc resection group, while in the intralesional excision group, the 5‐year local progression‐free survival rate was 80% with a 10‐year rate of 45.7%. The en bloc resection group had a lower local tumor recurrence rate than that of the intralesional excision group (p < 0.05), but the former had a higher rate of complications (p = 0.015). Conclusions This study revealed a low local recurrence rate in patients who underwent en bloc resection for giant cell tumors, while the perioperative complication rate was high.